OPTIMASI PROSES MASERASI VANILI (Vanilla planifolia Andrews) HASIL MODIFIKASI PROSES KURING [Maceration Process Optimation of Vanili (Vanilla Planifolia Andrews) from Modified Curing] - Dwi Setyaningsih; Meika S Rusli; Melawati .; Ika Mariska (Jurnal Teknologi dan Industri Pangan, 2006)
Modified cured vanilla was processed to vanilla extract by maceration method. The aim of this research were to optimize the method of maceration, type of vanilla bean with highest vanillin content, extraction solvent composition,and other variables that could optimize the vanillin content and characterize the extract from half dried cured vanilla. The optimation used response surface method with 22 factorial and 23 factorial. One step of maceration could extract vanillin (average 2.3 g/l) much more than two steps maceration (average 2.1 g/l). Vanillin content of the half dried cured vanilla (average 0.98 g/l) was higher than cured vanilla 1 and cured vanilla 2 (average 0.41 g/l and 0.32 g/l). The suitable ethanol-water composition for half dried cured vanilla was 7:3 (vanillin content 1.78 g/l). The first optimation was conducted with two variables maceration time and sucrose concentrations. The maximum vanillin content of the first optimation was 4.5 g/l at maceration time of15.9 days and sucrose concentration of 7.3 g. The second optimation used two variables: maceration time and glycerol concentrations. The maximum vanillin content of the second optimation was 3.8 g/l at maceration time of 22 days and glycerol concentration 19.9 ml. The third optimation process used three variables:maceration time, sucrose concentrations and glycerol concentrations. The maximum vanillin content of the third optimation was 3.4 g/l at maceration time of 12 days sucrose concentration of 7 g, and glycerol concentration 4.7 ml. The characteristic of vanilla extract resulted from half dried cured vanilla maceration were vanillin content (3.4-4.5 g/l), total acid (380-410 ml 0.1 N NaOH/l), total ash (1.3-3.4 g/l), total soluble ash (0.8-2.9 g/l), alkalinity of total ash (462.6-536.7), alkalinity of soluble ash (139.1-216.5), and lead number (4.5-4.6). Key words : Vanilla planifolia, Optimization, vanilla ekstrak